Dasatinib-induced renal (or chronic) thrombotic microangiopathy in a patient with chronic myeloid leukemia: A case report - Ryan Sabour; Sohrab Kharabaf; Eric Frazier; Matthew Nguyen; Dao Le; Jonathan Zuckerman; Ramy Hanna (SAGE Open Medical Case Reports)
Thrombotic microangiopathy encompasses microvascular thrombosis, hemolytic anemia, thrombocytopenia, and end-organ damage. Secondary thrombotic microangiopathy can result from malignancies, autoimmune diseases, or treatments such as tyrosine kinase inhibitors. Dasatinib, a tyrosine kinase inhibitor used in managing chronic myeloid leukemia, has been linked to thrombotic microangiopathy. This report describes a 66-year-old female with chronic myeloid leukemia treated with dasatinib who developed renal-limited thrombotic microangiopathy. Progressive renal dysfunction found in the context of chronic kidney disease prompted extensive lab evaluation and evaluation, with a renal biopsy confirming thrombotic microangiopathy attributed to dasatinib-induced nephrotoxicity. Discontinuation of dasatinib led to a slight improvement in renal function; however, progressive decline necessitated dialysis. This case underscores the diagnostic and therapeutic challenges of dasatinib-induced thrombotic microangiopathy, emphasizing renal biopsy in diagnosis and monitoring. Individualized treatment strategies and further research should be conducted to optimize future outcomes.